2007
DOI: 10.1088/0951-7715/20/7/010
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian particle paths and ortho-normal quaternion frames

Abstract: Experimentalists now measure intense rotations of Lagrangian particles in turbulent flows by tracking their trajectories and Lagrangian-average velocity gradients at high Reynolds numbers. This paper formulates the dynamics of an orthonormal frame attached to each Lagrangian fluid particle undergoing three-axis rotations, by using quaternions in combination with Ertel's theorem for frozen-in vorticity. The method is applicable to a wide range of Lagrangian flows including the three-dimensional Euler equations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 38 publications
3
31
0
4
Order By: Relevance
“…(26) has its origins in the divergence-free condition Tr M = 0 and is an economical way of writing ∆ p = −u i, j u j,i . Several attempts have been made to model the Lagrangian-averaged pressure Hessian by introducing a constitutive closure -see [78] for a summary. The idea goes back to Léorat [79], Vieillefosse [80], Novikov [81] and Cantwell [82].…”
Section: Restricted Euler Equations: Modelling the Pressure Hessianmentioning
confidence: 99%
See 3 more Smart Citations
“…(26) has its origins in the divergence-free condition Tr M = 0 and is an economical way of writing ∆ p = −u i, j u j,i . Several attempts have been made to model the Lagrangian-averaged pressure Hessian by introducing a constitutive closure -see [78] for a summary. The idea goes back to Léorat [79], Vieillefosse [80], Novikov [81] and Cantwell [82].…”
Section: Restricted Euler Equations: Modelling the Pressure Hessianmentioning
confidence: 99%
“…Other models of interest include the tetrad model of Chertkov, Pumir and Shraiman [88] which has recently been developed by Chevillard and Meneveau [89]. More ideas regarding the modelling of the pressure Hessian through a transformation from Eulerian to Lagrangian coordinates using a Lagrangian flow map have recently been discussed in [78].…”
Section: Restricted Euler Equations: Modelling the Pressure Hessianmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were based on earlier work by McIntyre and Roulstone, and were reviewed by them in McIntyre & Roulstone (2002). It has also been shown that the three-dimensional Euler equations has a quaternionic structure in the dependent variables (Gibbon 2002) and that this idea can be used to discuss the evolution of orthonormal frames on particle trajectories: see Gibbon et al (2006), Gibbon (2007Gibbon ( , 2008a and Gibbon & Holm (2007). The use of different sets of dependent and independent variables in geophysical models of cyclones and fronts has facilitated some remarkable simplifications of otherwise hopelessly difficult nonlinear problems: see Hoskins & Bretherton (1972).…”
Section: Equations For An Incompressible Fluidmentioning
confidence: 99%